Photochromic dynamics of organic–inorganic hybrids supported on transparent and flexible recycled PET - Cruz, R. P.; Nalin, M. [UNESP]; Ribeiro, S. J.L. [UNESP]; Molina, C. (Elsevier, 2017)
Organic–inorganic hybrids (OIH) synthesized by sol gel process containing phosphotungstic acid (PWA) entrapped have been attracted much attention for ultraviolet sensitive materials. However, the limitations for practical photochromic application of these materials are the poor interaction with flexible polymer substrates such as Poly(ethyleneterephthalate) (PET) and also photo response under ultraviolet radiation. This paper describes the use of the d-ureasil HOI, based on siliceous network grafted through linkages to both ends of polymer chain containing 2.5 poly(oxyethylene) units with PWA entrapped prepared as films on recycled PET. Films were characterized by IR-ATR, XRD, TG/DTG, UV–Vis and Contact angle. XRD patterns showed that both pristine hybrid matrix and those containing PWA are amorphous. IR showed that PWA structure is preserved in the matrix and interactions between them occur by intermolecular forces. Films are thermally stable up to 325 °C and contact angle of 25.1° showed a good wettability between substrate and hybrid matrix. Furthermore, films showed fast photochromic response after 1 min of ultraviolet exposure time. The bleaching process revealed that the relaxation process is dependent of the temperature and the activation energy of 47.2 kJ mol−1 was determined. The properties of these films make them potential candidates for applications in flexible photochromic materials.
Keywords: Hybrids; Photochromic; Polyoxometalates; Sol–gel; Transparent recycled PET